2015
DOI: 10.1136/annrheumdis-2015-207841
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic infections and biologic therapies in immune-mediated inflammatory diseases: consensus recommendations for infection reporting during clinical trials and postmarketing surveillance

Abstract: No consensus has previously been formed regarding the types and presentations of infectious pathogens to be considered as 'opportunistic infections' (OIs) within the setting of biologic therapy. We systematically reviewed published literature reporting OIs in the setting of biologic therapy for inflammatory diseases. The review sought to describe the OI definitions used within these studies and the types of OIs reported. These findings informed a consensus committee (infectious diseases and rheumatology specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 63 publications
0
115
0
5
Order By: Relevance
“…37 Rates of fungal and viral OIs were similar to those previously reported, 20 suggesting OIs are a risk with tofacitinib, although it is unclear whether risk differs from that associated with bDMARDs. Precise estimations of differences in OI risk among RA therapies are limited by heterogeneous definitions of OIs, 38 geographical variability and lack of head-to-head studies with sufficient power to detect differences. A higher incidence of TB has been observed in patients with RA versus the general population, and in those receiving TNFi.…”
Section: Discussionmentioning
confidence: 99%
“…37 Rates of fungal and viral OIs were similar to those previously reported, 20 suggesting OIs are a risk with tofacitinib, although it is unclear whether risk differs from that associated with bDMARDs. Precise estimations of differences in OI risk among RA therapies are limited by heterogeneous definitions of OIs, 38 geographical variability and lack of head-to-head studies with sufficient power to detect differences. A higher incidence of TB has been observed in patients with RA versus the general population, and in those receiving TNFi.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous meta-analyses have evaluated the general risk of serious infections or opportunistic infections, defined as development of a mycobacterial, fungal, or viral infection, during treatment with biologics and/or nbDMARDs. These studies have shown a clear risk of granulomatous infections, such as tuberculosis with biologics, but not necessarily for viral infections, although this may be related to lack of standardized reporting in RCTs [8, 76, 78, 79]. There were insufficient RCT data to enable us to examine HZ risk according to specific biological agents, but we did stratify our analysis according to the type of biologic and found evidence of a greater risk of HZ with non-TNF biologics.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the RCTs being underpowered to detect differences in rare AEs such as HZ [79]. The types of nbDMARD used in the trials and clinical practice vary considerably, and our meta-analysis studies included 8 different nbDMARDs, because such we were not able to stratify results by drug, other than tofacitinib, which had enough RCTs for us to pool the results.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding OIs were retrieved from the patients’ medical records and were defined in accordance with a recently published consensus document describing the specific pathogens and clinical presentations that ‘indicate’ the likelihood of a host immune abnormality in the setting of immunosuppressive therapy …”
Section: Methodsmentioning
confidence: 99%
“…Data regarding OIs were retrieved from the patients' medical records and were defined in accordance with a recently published consensus document describing the specific pathogens and clinical presentations that 'indicate' the likelihood of a host immune abnormality in the setting of immunosuppressive therapy. 16 The standard treatment in our DM/PM patients includes administration of glucocorticoids (1 mg/kg/ day) plus at least one of the following immunosuppressive drugs: azathioprine, methotrexate, cyclosporine, tacrolimus, cyclophosphamide (pulses) and mycophenolate mofetil. Various therapeutic approaches are used in refractory myositis patients: switching from one drug to another, adding another immunosuppressive drug to the first one, and/or use of biological therapy with infliximab, adalimumab, etanercept or rituximab.…”
Section: Opportunistic Infectionsmentioning
confidence: 99%